Deconstructing context-sensitive nature of Indians'behaviour: a preliminary attempt to develop a taxonomy for three work contexts. (1st January 2012) - Panda, Abinash; Gupta, Rajen K.
Indians are perceived to be highly contradictory and inconsistent in their manifested behavioural patterns. Findings of various research studies have indicated that at the core of perceived 'contradictions' in the manifested behavioural patterns of the Indians lies in the fact that Indian behaviour is determined more by the situation or the context rather than the personality. Sinha and Kanungo (1997) mentioned that 'context sensitivity among Indians manifests itself in relation to three components of the environment, which are desh (place), kal (time) and patra (person). Sinha et al. (2002) have urged scholars to attempt a more systematic taxonomy of situations to develop generalised cultural modes of behaviour. This paper is at best a baby step in that direction. In this paper, we have attempted to deconstruct the context sensitive behaviour of Indians using an 'interactional' framework and subsequently presented a behavioural taxonomy, which would help understand how Indians with different worldviews would behave in different work contexts. We have identified three ideal types of Indians, who are the products of their early socialisations. The three work contexts, we have identified in this paper are three different kinds of business organisations namely family owned, government and Western multinational organisations.